AIDS-Related Central Nervous System Toxoplasmosis With Increased 18F-Fluoroethyl-L-Tyrosine Amino Acid PET Uptake Due to LAT1/2 Expression of Inflammatory Cells. (December 2017) - Hutterer, Markus; Bumes, Elisabeth; Riemenschneider, Markus J.; Grosse, Jirka; Hellwig, Dirk; Galldiks, Norbert; Langen, Karl-Josef; Hau, Peter
Abstract : Abstract: We report the case of a 40-year-old woman with a progressive right-sided hemiparesis. Standard MRI revealed a contrast-enhancing brain lesion within the left basal ganglia. 18 Ffluoroethyl-L-tyrosine ( 18 F-FET) PET showed a distinct tracer uptake (lesion-to-brain ratio [LBR]: LBRmax = 2.03, LBRmean = 1.68) with a significant larger metabolic lesion volume than contrast-enhancement in MRI, indicating cerebral glioma. Surprisingly, histopathologic analysis demonstrated central nervous system toxoplasmosis with pronounced inflammatory reaction (reactive astrogliosis, microglia activation, macrophage, and T-lymphocyte infiltration), which was associated with strong LAT1/LAT2/CD98 expression. In conclusion, inflammatory brain lesions, such as cerebral toxoplasmosis, represent a potential pitfall of 18 F-FET PET mimicking a brain tumor.